Practices of Midwives in the Use of Personal Protective Equipment when Aid Labor during the COVID-19 Pandemic - Shinta Novelia; Rosmawati Lubis; Reni Murniati; Bunga Tiara Carolin (Nursing and Health Sciences Journal (NHSJ), 2021)
Background: In the era of the COVID-19 pandemic, the use of personal protective equipment (PPE) is very important to reduce the risk of transmitting infectious diseases to medical personnel because it can prevent contact with pathogens. This shows that midwives as first-line managers of pregnancy, childbirth and postpartum cases must be vigilant by wearing complete Personal Protection Equipment (PPE) so that there is no transmission of the virus from the patient to the midwife. Objective: To determine the analysis of midwives' practices in using PPE when assisting labor during the COVID-19 pandemic at the Banten Regional General Hospital 2020-2021. Methodology: A quantitative analytic study using a cross sectional approach. The sample in this study was 102 respondents with purposive sampling technique. Data were analyzed using SPSS with Chi Square, which previously tested the validity and reliability. Results: The use of PPE in midwives in Banten Hospital obtained an average value of 84.3. Based on age, the average value was 53.9. Based on the length of service, the average score was 96.1. Based on education, the average score is 55.9. The results of the chi-square test showed that all independent variables had no relationship with the use of PPE including knowledge (p = 0.323), attitude (p = 0.665), availability of PPE (p = 0.740), and supervision (p = 0.603). Conclusions and Suggestions: The use of PPE in midwives has no relationship with knowledge, attitudes, availability of PPE and supervision. There is a need for socialization about the importance of using PPE to midwives in order to maintain the quality of expected care services. There is a need for an K3 unit in Banten Hospital which is one of the authorities. There needs to be special attention from the Hospital Management regarding the supervision of the use of PPE in midwives.